STRATEGI KOPING SISWA DALAM MENGHADAPI STRES AKADEMIK DI ERA PANDEMI COVID-19 - Della Tri Damayamti; Alviyatun Masitoh (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Academic stress is a condition due to an imbalance of the desired situation with the physiological, psychological, and social system of students, so the problem of academic stress must be resolved immediately. This study aims to determine the causal factors and studentsâ€™ strategies in reducing the threat that burdens them due to stress in the Covid-19 pandemic era. The research subjects were three students of class XII. The results of this study indicate that the three students have similar coping strategies. Problem focused coping are manifested through planful problem solving and seeking social support. While emotion focused coping through positive reappraisal and self control. Then, the researchers identified another form of coping strategy in one of the subjects, namely religious coping in the form of tawakal and qanaah.Keywords:Â academic stress; coping strategy; Covid-19; high school student